A Boolean Model in information retrieval for search engines - Lashkari, A.H.; Mahdavi, F.; Ghomi, V. (2009)
An information retrieval (IR) process begins when a user enters a query into the system. Queries are formal statements of information needs, for example search strings in web search engines. In IR a query does not uniquely identify a single object in the collection. Instead, several objects may match the query, perhaps with different degrees of relevancy.